iCare benefits: Assisting low income retail consumers in Vietnam – Part A - THOMAS, Howard (Institutional Knowledge at Singapore Management University, 2019)
Case A is set in 2016. Trung Dung is the founder of iCare Benefits (iCare), a social enterprise established to aid low-income workers. His background included studying computer science in the US and successfully working in the American software industry. Trung returned to Vietnam to discover that many low-income workers had to borrow heavily for basic household necessities, especially migrant workers who moved to the city with nothing. How could he help? Trung decided to tackle the related problems of lack of access to the formal financial sector and the workers’ lack of basic consumer durable goods. He partnered with employers, global manufacturers and financial institutions to develop a third-party employee benefits programme that would help low-income migrant workers afford basic goods. iCare would undertake retail functions to enable migrant workers to buy consumer goods. Using an innovative retail model, iCare would provide workers with zero-interest procurement loans for up to six months. His value proposition to partners allowed for a collaborative setup that permitted the social enterprise to operate without donations. Case B continues in 2018. iCare has been successful in reducing borrowing from other sources at usurious rates. Many workers now have access to financing and consequently basic consumer durable goods. Trung is able to scale up and reach many more workers. However, he wanted to help existing members as well. He would start to offer additional consumer discretionary products and services in the areas of education, healthcare and insurance. How might he further improve the lives of low income workers? After studying the case, students will understand how iCare’s innovative retail model was different from the traditional model; Differentiate social entrepreneurships from for-profit organisations and not-for-profit organisations and compare the social impact of social entrepreneurship from a social service provider and a social activist; Understand the motivations of people as their basic needs are fulfilled.